CD39 expression by hepatic myeloid dendritic cells attenuates inflammation in liver transplant ischemia‐reperfusion injury in mice. Issue 6 (15th October 2013) - Yoshida, Osamu; Kimura, Shoko; Jackson, Edwin K.; Robson, Simon C.; Geller, David A.; Murase, Noriko; Thomson, Angus W.
<x xml:space="preserve">Abstract</x> Hepatic innate immune cells, in particular, interstitial dendritic cells (DCs), regulate inflammatory responses and may promote inherent liver tolerogenicity. After tissue injury, adenosine triphosphate (ATP) is released and acts as a damage‐associated molecular pattern that activates innate immune cells by pattern recognition receptors. CD39 (ectonucleoside triphosphate diphosphohydrolase‐1) rapidly hydrolyzes extracellular ATP to maintain physiological levels. We hypothesized that CD39 expression on liver DCs might contribute to regulation of their innate immune functions. Mouse liver conventional myeloid DCs (mDCs) were hyporesponsive to ATP, compared with their splenic counterparts. This disparity was ascribed to more efficient hydrolysis of ATP by higher expression of CD39 on liver mDCs. Human liver mDCs expressed greater levels of CD39 than those from peripheral blood. The comparatively high expression of CD39 on liver mDCs correlated strongly with both ATP hydrolysis and adenosine production. Notably, CD39−/− mouse liver mDCs exhibited a more mature phenotype, greater responsiveness to Toll‐like receptor 4 ligation, and stronger proinflammatory and immunostimulatory activity than wild‐type (WT) liver mDCs. To investigate the role of CD39 on liver mDCs in vivo, we performed orthotopic liver transplantation with extended cold preservation using CD39−/− or WT donor mouse livers. Compared to WT liver grafts, CD39−/− grafts exhibited enhanced interstitial DC activation, elevated proinflammatory cytokine levels, and more‐severe tissue injury. Moreover, portal venous delivery of WT, but not CD39−/− liver mDCs, to donor livers immediately post‐transplant exerted a protective effect against graft injury in CD39−/− to CD39−/− liver transplantation. Conclusions: These data reveal that CD39 expression on conventional liver mDCs limits their proinflammatory activity and confers protective properties on these important innate immune cells against liver transplant ischemia/reperfusion injury. (Hepatology 2013; 58:2163–2175)